From Parent to Child: Early Labor Market Experiences of Second-Generation Immigrants in the Netherlands - Jan C. van Ours; Justus Veenman (Institute for the Study of Labor (IZA), 2002)
This paper is on the early labor market experiences of second-generation immigrants in the Netherlands. We find that only for employment rates there are some differences a cross ethnic groups. Conditional on having a job there is hardly any difference in wages and other job characteristics between second-generation immigrants and native Dutch of the same age group.
Keywords: J15; J61; 330; second-generation immigrants; ethnic minorities; labor market; Ethnische Gruppe; Arbeitsmarkt; Lohnniveau; Arbeitslosigkeit; Generationenbeziehungen; Niederlande